Proceso de atención de enfermería en paciente con ruptura prematura de membrana. - Romero Cedeño, Andrea Vanessa (2021)
There are several premature ruptures of the membrane, one of them is recognized by its acronym in English as PROM, where it is understood as a rupture of ovular membranes and this occurs before the gestation has reached active labor. If the product has not reached term, it is called preterm premature rupture of membranes (PPROM), a prolonged PROM can also occur, it is identified when twenty-four hours or more are exceeded from the start of labor. This premature rupture of the membrane is one of the complications that usually occurs in obstetric practice, however, it may have an increase in its incidence within the maternal-fetus morbidity and mortality rate, related to puerperal infections. It can also be observed that the origin of premature ruptures of membranes corresponds to various factors, the same ones that are involved during the course of pregnancy.